Counseling Needs of Battered Women and Counseling Strategies: A Study by a Feminist Counselor - Cauyan, Jaclyn Marie L. (Review of Women's Studies, 2023)
Violence Against Women (VAW) is prevalent in every society and domestic violence is its most pervasive form. In the Philippines, domestic violence cases involving countless of women who experience abuse from their partners are reported every day by various government and non-government agencies. Such abuses have varying effects on the self-concept and level of empowerment of these women. In this study, ten battered women were interviewed to determine the nature of trauma they have experienced and their corresponding counseling needs. Results show that the women suffered physical, sexual, and psychological/ emotional trauma. Their counseling needs included: 1) crisis intervention and management, 2) improvement of low self-concept and low level of empowerment, 3) dealing with a myriad of feelings (i.e., loneliness, grief, failure as a woman, mother and wife) and conflicting feelings (i.e., love, anger/hatred) for their partner, 4) work or employment support, and 5) post-crisis management. To address the participants' needs, feminist counseling was employed by the counselor-researcher focusing on four concrete strategies: 1) valuing women, 2) building an egalitarian relationship between the client and the counselor, 3) consciousness-raising, and 4) crisis interventions and management. Examples on how these strategies were applied to particular cases of the participants are likewise provided.